Disc-fovea Angle Is Associated With Visual Field Defect Location in Patients With Glaucoma. Issue 10 (October 2020) - Abe, Ricardo Y.; Matos, Alexis G.; Gracitelli, Carolina P.B.; Prata, Tiago S.; Ribeiro, Guilherme B.; Paula, Jayter S.
Abstract : Precis: The current study showed that glaucomatous eyes from patients with central visual field defects presented less negative disc-fovea angle compared with patients with peripheral defects. Purpose: The purpose of this study was to investigate the relationship between disc-fovea angle and visual field defect location in patients with glaucoma. Materials and Methods: This was a cross-sectional study including glaucoma patients divided into isolated central and isolated peripheral scotoma groups. The main outcome measure was disc-fovea angle measurement between groups. Secondary outcomes included disc-fovea distance, vertical disc diameter, and fovea vertical deviation. Results: We included 50 glaucoma patients (50 eyes; 27 with central scotoma and 23 with peripheral scotoma). Mean deviation from visual fields was −3.05±1.67 and −2.95±1.49 dB ( P =0.829) (central and peripheral scotoma groups, respectively). We found that eyes in the central group had lower values of disc-fovea angle (−5.85±2.67 vs. −7.97±2.26 degrees, P =0.004), shorter disc-fovea distance (4.38±0.70 vs. 4.98±0.78 mm, P =0.006), and shorter fovea vertical deviation (−0.43±0.19 vs. −0.68±0.22 mm, P <0.001) compared with eyes in the peripheral group. Conclusions: This study showed an association between disc-fovea angle and central visual field defects in patients with glaucoma. Our findings suggest that eyes with a less negative disc-fovea angle should undergo a more careful investigation of the central visual field, even at early stages of the disease.